The rare green‐blue neutrophil inclusion bodies. Worth reporting in blood films? A case of a patient with polytrauma. Issue 12 (16th July 2020) - Bowen, Rebecca Katrina; Koutsavlis, Ioannis
Abstract: Blood films are an easy tool to aid the diagnosis and management of unwell patients and should be prepared in this setting. Green‐blue neutrophil inclusion bodies could be an ominous sign of poor prognosis in critically ill patients. Abstract : Blood films are an easy tool to aid the diagnosis and management of unwell patients and should be prepared in this setting. Green‐blue neutrophil inclusion bodies could be an ominous sign of poor prognosis in critically ill patients.